2016
DOI: 10.1080/10245332.2016.1193962
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated microRNA expression and its pathogenetic implications for myelodysplastic syndromes

Abstract: Although the function of miRNAs is not fully understood, these small non-coding RNAs represent novel pathogenetic and clinical implications in MDS. The studies of miRNAs may guide us towards a better understanding of this disease and shed light on the development of new therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 85 publications
0
20
0
Order By: Relevance
“… 107 It has been found that miR181c, miR181a, miR181b, and miR181d are selectively overexpressed in high-risk cases of MDS. 108 The literature also reports upregulation of miR720 and miR21, whereas levels of miR210 and miR155 are increased in CD34 + MDS cells. 109 111 At the same time, decreased expression of the Let7 family of microRNAs was shown.…”
Section: Microrna Expression In Chronic Myelogenous Leukemiamentioning
confidence: 99%
“… 107 It has been found that miR181c, miR181a, miR181b, and miR181d are selectively overexpressed in high-risk cases of MDS. 108 The literature also reports upregulation of miR720 and miR21, whereas levels of miR210 and miR155 are increased in CD34 + MDS cells. 109 111 At the same time, decreased expression of the Let7 family of microRNAs was shown.…”
Section: Microrna Expression In Chronic Myelogenous Leukemiamentioning
confidence: 99%
“…Given their regulatory role, miRNAs have been evaluated in samples obtained from MDS patients, sAML patients, and healthy donors. Comparative studies revealed a differential miRNA expression pattern between these three groups [ 16 , 92 ] ( Table 1 ). These studies were carried out to identify (i) diagnostic and prognostic markers for these diseases, (ii) biomarkers indicative of the progression from MDS to sAML, and (iii) novel therapeutic targets.…”
Section: Mirna Expression In Mds and Samlmentioning
confidence: 99%
“…MDS is regarded as a disease preceding leukemia and about 30% of patients with MDS eventually develop AML [ 24 ]. Analysis of literature data showed that miRNA expression profiles differ between early and advanced stages of MDS, suggesting the involvement of miRNAs in the pathogenesis of MDS and, consequently, in MDS-to-AML transformation [ 99 ]. The expression levels of miRNA-27a-3p, −150-5p, −199a-5p, −223-3p and miRNA-451a are reduced in the plasma of high-risk patients with MDS, while miRNA-196b-5p is enhanced in BM specimens from a higher-risk patient with MDS, suggesting that these miRNAs may be used as biomarkers predicting the risk of further transformation of MDS [ 100 , 101 ].…”
Section: Mirna In the Prognosis Of Mdsmentioning
confidence: 99%